2011
DOI: 10.4330/wjc.v3.i3.72
|View full text |Cite
|
Sign up to set email alerts
|

Renin and cardiovascular disease: Worn-out path, or new direction

Abstract: Inhibition of the renin angiotensin system has beneficial effects in cardiovascular prevention and treatment. The advent of orally active direct renin inhibitors adds a novel approach to antagonism of the renin-angiotensin system. Inhibition of the first and rate-limiting step of the renin angiotensin cascade offers theoretical advantages over downstream blockade. However, the recent discovery of the (pro)renin receptor which binds both renin and prorenin, and which can not only augment catalytic activity of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…This relatively small decrease in MAP may be due to the lack of significant downregulation in renal angiotensinogen or renin expression in EMPA-treated PCOS rats. The conversion of angiotensinogen to angiotensin I by renin is the rate-limiting step of the RAS [ 38 ]. Woods et al showed that decreased angiotensinogen was associated with decreased BP by SGLT2 inhibition in males in a T2DM model [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This relatively small decrease in MAP may be due to the lack of significant downregulation in renal angiotensinogen or renin expression in EMPA-treated PCOS rats. The conversion of angiotensinogen to angiotensin I by renin is the rate-limiting step of the RAS [ 38 ]. Woods et al showed that decreased angiotensinogen was associated with decreased BP by SGLT2 inhibition in males in a T2DM model [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As two antihypertensives in the involvement of renin angiotensin system (RAS), they have similar mechanisms. ACEIs could reduce production of angiotensin (Ang) II by inhibiting angiotensin converting enzyme, a key enzyme affecting the transformation from angiotensin I to angiotensin II [36] . Also, the inhibition of the angiotensin converting enzyme also increased bradykinin production [37] .…”
Section: Discussionmentioning
confidence: 99%
“…ACEIs improve endothelial function by reducing the production of angiotensin II by inhibiting angiotensin converting enzyme, a key enzyme affecting the transformation from angiotensin I to angiotensin II and increasing bradykinin production (71,72). A meta-analysis of randomized controlled trials demonstrated that ACEIs improve peripheral endothelial function and are superior to other anti-hypertensive drugs including calcium channel blockers and β-blockers (73).…”
Section: Therapeutic Approachesmentioning
confidence: 99%